Personal Data Protection in the Digital Age: An Analysis of Constitutionalism in E-Commerce Towards Harmonization of Regulations - Okky Andaniswari; Dewi Sulistianingsih; Pujiono Pujiono (Pandecta Research Law Journal, 2026)
The advancement of the digital era has brought significant changes to trade activities, particularly in the shift from conventional trading systems to faster and more precise electronic commerce (e-commerce). The study has revealed this new information regarding personal data protection information. As a result, the national legal system must control the growth of e-commerce while adhering to the strictest constitutional law requirements.  adhere to the strictest requirements of constitutional law while being governed by the national legal system. Law is essential to ensure that consumer rights are upheld and that businesses operate transparently and ethically. This balance will foster trust in e-commerce platforms and encourage their growth in a secure environment. This study uses normative juridical and conducts descriptive-analytical data analysis. It also uses theories, concepts, and principles of digital constitutionalism. This study aims to ascertain and evaluate the degree to which existing legislation offers legal certainty for safeguarding personal information in the context of online transactions. This study will look at current legal frameworks and how well they handle the problems brought on by the quick advancement of e-commerce technology. The results demonstrate that e-commerce rules are still dispersed throughout many laws and regulations, which raises questions about legal ambiguity and the security of personal information in e-commerce transactions.  In order to resolve this difficulty and construct a cohesive and legally sound regulatory framework based on constitutionalism, a special statute that fully regulates electronic commerce must be established.